2022
DOI: 10.1117/1.jbo.27.5.056502
|View full text |Cite|
|
Sign up to set email alerts
|

Unsupervised super-resolution reconstruction of hyperspectral histology images for whole-slide imaging

Abstract: . Significance: Hyperspectral imaging (HSI) provides rich spectral information for improved histopathological cancer detection. However, acquiring high-resolution HSI data for whole-slide imaging (WSI) can be time-consuming and requires a huge amount of storage space. Aim: WSI using a color camera can be achieved with fast speed, high image resolution, and excellent image quality due to the established techniques. We aim to develop an RGB-guided unsupervised hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…In the bottom row, we show the same whole slides captured using our own HWSI system. The images in the bottom row are shown in synthesized-RGB using a method previously reported by us [15] to produce colored images from hyperspectral images. These HWSI are composited by using 80 -120 hyperspectral images, each individual hyperspectral image is of size 84 × 2000 × 2000 pixel.…”
Section: Quality Of Acquisitionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the bottom row, we show the same whole slides captured using our own HWSI system. The images in the bottom row are shown in synthesized-RGB using a method previously reported by us [15] to produce colored images from hyperspectral images. These HWSI are composited by using 80 -120 hyperspectral images, each individual hyperspectral image is of size 84 × 2000 × 2000 pixel.…”
Section: Quality Of Acquisitionmentioning
confidence: 99%
“…Preliminary research shows that training histopathology classifiers using hyperspectral images yield better cancer margin compared to that trained on RGB images [9][10][11][12][13][14]. Ma et al [15,16] showed that using hyperspectral images of head and neck squamous cell carcinoma to train neural networks can result in improvements of patch-wise classification over using regular RGB images. Ortega et al [17,18] used hyperspectral imaging and deep learning techniques to detect breast cancer and brain cancer (glioblastoma) in histological slides.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We utilized hematoxylin and eosin (H&E)-stained histological slides as well as their corresponding digital histologic images obtained from four different head and neck squamous cell carcinoma (SCC) patients who underwent routine surgery [14]. Each patient has one slide of normal tissue (N) and one slide of tumor tissue (T), which were imaged using an automated hyperspectral microscopic imaging system [11]. Hyperspectral images were acquired with a 40× objective magnification.…”
Section: Histologic Slides and Hyperspectral Datasetmentioning
confidence: 99%
“…In the past, several studies tried to synthesize hyperspectral images from RGB images, since RGB images were relatively easier to acquire [9,10]. However, as the significance of HSI being recognized in recent years, some automated or semi-automated hyperspectral microscopic imaging systems have been developed [6,[11][12][13], which can implement the acquisition of high-quality digital hyperspectral histologic images for computational pathology purposes. Although two imaging modalities can be integrated into one system, i.e., both the hyperspectral and color cameras can be mounted onto a microscope and acquire both HSI and RGB images simultaneously, it can be more cost effective if only one camera is needed.…”
Section: Introductionmentioning
confidence: 99%